Presence of antibiotic resistance genes in different salinity gradients of freshwater to saltwater marshes in southeast Louisiana, USA. (September 2016) - Bergeron, Scott; Brown, Ryan; Homer, Justin; Rehage, Sarah; Boopathy, Raj
Abstract: One of the major public health problems facing the world today is the occurrence and spread of antibiotic resistant bacteria (ARB) in the environment. The main reservoir for ARB is the aquatic ecosystems. Culture based methods and qualitative molecular techniques were used to screen and determine the presence of antibiotic resistance genes (ARG) and ARB in three different salinity gradients of wetland marsh in the southeast Louisiana of USA. The bacteria of interest include Enterobacter cloacae/aerogenes, Enterococci spp. and Escherichia coli . The antibiotic resistance genes of interest include ermB, sul1, tetA, tetX, tetW, and mecA that are responsible for resistance to erythromycin, sulfonamide, tetracycline, and methicillin antibiotics. The water salinity ranged from 0 to 12 parts per thousand (ppt). Monthly samples were taken for a six-month period and analyzed for the presence of ARB and ARGs along with carbon, nitrogen, and phosphorous levels in the water samples. The results indicated salinity did not have significant difference in the presence of ARB and ARGs in the wetlands. Significant numbers of ARB were found in all three salinity levels (0, 6, and 12 ppt) in the marshes of Southeast Louisiana. ARGs were more prevalent in site 2 with the salinity of 6 ppt followed by site 1 with the salinity of 12 ppt and site 3 with 0 ppt salinity. Bacterial load and the pollution load varied from month to month and among the three salinities. This study indicates the presence of ARB and ARGs in the wetland habitat is a cause for concern as the potential threat of the spread of ARGs into native bacteria and into fish and wildlife exists due to human activities even under high salinity habitat. Highlights: Effect of salinity on antibiotic resistant bacteria (ARB) was studied. Salinity did not affect the presence of ARB. ARGs were found in the wetlands with various salinities.